Mao the real story - Pantsov, Alexander (New York Simon & Schuster, 2012)
Mao Zedong was one of the most important figures of the twentieth century, the most important in the history of modern China. A complex figure, he was champion of the poor and brutal tyrant, poet and despot.
Includes bibliographical references (p. [675]-713) and index.
Keywords: Mao, Zedong, 1893-1976.